S-PTAM: Stereo Parallel Tracking and Mapping - Pire, Taihú Aguará Nahuel (2017)
This paper describes a real-time feature-based stereo SLAM system that is robust and accurate in a wide variety of conditions – indoors, outdoors, with dynamic objects, changing light conditions, fast robot motions and large-scale loops. Our system follows a parallel-tracking-and-mapping strategy: a tracking thread estimates the camera pose at frame rate; and a mapping thread updates a keyframe-based map at a lower frequency. The stereo constraints of our system allow a robust initialization – avoiding the well-known bootstrapping problem in monocular systems–and the recovery of the real scale. Both aspects are essential for its practical use in real robotic systems that interact with the physical world. In this paper we provide the implementation details, an exhaustive evaluation of the system in public datasets and a comparison of most state-of-the-art feature detectors and descriptors on the presented system. For the benefit of the community, its code for ROS (Robot Operating System) has been released.